Quest for the presidency : the storied and surprising history of presidential campaigns in America - Riel, Bob (Potomac Books, an imprint of the University of Nebraska Press, 2022)
""Quest for the Presidency" is an engaging and, at times, amusing popular history of American presidential elections from 1789 to the present that offers insight into the impact past elections have on today's politics"--